Nipple Sparing Mastectomy as a Risk-Reducing Procedure for BRCA-Mutated Patients - Rocco, Nicola (Genes (Basel), 2021)
Growing numbers of asymptomatic women who become aware of carrying a breast cancer gene mutation (BRCA) mutation are choosing to undergo risk-reducing bilateral mastectomies with immediate breast reconstruction. We reviewed the literature with the aim of assessing the oncological safety of nipple-sparing mastectomy (NSM) as a risk-reduction procedure in BRCA-mutated patients. Nine studies reporting on the incidence of primary breast cancer post NSM in asymptomatic BRCA mutated patients undergoing risk-reducing bilateral procedures met the inclusion criteria. NSM appears to be a safe option for BRCA mutation carriers from an oncological point of view, with low reported rates of new breast cancers, low rates of postoperative complications, and high levels of satisfaction and postoperative quality of life. However, larger multi-institutional studies with longer follow-up are needed to establish this procedure as the best surgical option in this setting.